Doctor-patient relationship: effectiveness of an intervention training module on knowledge and attitude of resident doctors - Chavan, Kalidas D.; Giri, Purushottam A.; Mumbre, Sachin S.; Bangal, Rajendra S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The mutual trust between doctor and patient, an indispensable part of the healthcare, is weakening day by day. This has resulted in unwanted incidences of violence and attacks on doctors. Communication between doctors and patients is an integral part of the relationship and is one of the major determinants of mutual trust. Apart from the knowledge and skills required to treat a disease, communication skill is an indispensable part of a doctor’s professional life. The resident doctors do not get a chance to learn and implement the communication skills required for the doctor patient relationship. Methods: An interventional study was carried out amongst 377 resident doctors of first to third year, from randomly selected medical colleges of Maharashtra having postgraduate courses in clinical subjects and affiliated to Maharashtra University of Medical Sciences, Nashik, Maharashtra during the period of February 2017 to January 2019. Results: There was significant difference in the pre and post test scores for quantified knowledge in relation to training in communication skills (p<0.0001), and also significant difference in the pre and post test scores for quantified knowledge in relation to basic doctor patient relationship, suggesting that the intervention was effective in improving the communication skills. Conclusions: The study has shown that there was significant difference in the pre and post test scores for quantified knowledge in relation to being doctor, basics of communication skills, doctor patient relationship, communication in special situation, and training in communication skills.